FUNDRAISING DANA ZAKAT DI BADAN AMIL ZAKAT NASIONAL CABANG BANYUWANGI - Subaidi Subaidi; Subyanto Subyanto (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2024)
Fundraising is an activity to organize zakat in accordance with the management function in an effort to distribute it from muzakki to mustahiq so that organizational goals are created effectively and the goals of zakat can be achieved. The distribution of zakat at BAZNAS Banyuwangi to mustahiq is carried out in accordance with Islamic law by considering the priority scale of mustahiq needs in the form of consumptive aids. It means that helping mustahiq in solving their very urgent basic economic problems, and productive aids in order to improve welfare, both individually and in groups through ongoing activities or programs.